Risk Factors of Diarrhea in Children Under Five Years in Urban Slums: An Epidemiological Study - Kalakheti, Balakrishna; Panthee, Kiran; Jain, Kastur Chand (Journal of Lumbini Medical College, 2017)
Introduction: Diarrhea is a leading cause of mortality in children in developing countries and the condition is worse in slums. In order to provide effective preventive and management strategies, it is important to identify factors associated with the disease. This study was carried out to investigate the risk factors of diarrhea in children under five years of age in urban slums. Methods: Parents of all children under five years from the urban slums of Tansen municipality, Palpa, Nepal were interviewed using a standardized pretested questionnaire and proforma. Parental variables, environmental factors, and presence of diarrhea in those children in past three months were collected by trained enumerators and the data were analyzed with statistical software SPSS-10. Results: A total of 450 under five years children were enrolled in the study. There were 216 (48%) male and 234 (52%) female children with F:M ratio of 1.08:1. Occurrence of diarrhea was lower if the children were breast-fed for more than six months, well-nourished, used fountain water for drinking, or used boiled or treated water. Similarly, diarrhea prevalence was lower if father had a regular job, daily income in the family was more than one US dollar, there was a toilet in the house, practice of hand washing was followed before feeding or preparing food, or there was no child suffering from diarrhea in the neighborhood. Conclusion: There are a few variables that are significantly related to diarrhea in children under five years of age. In order to decrease the diarrheal episodes in children in the slums of the developing countries, priority could be given in the improvement of those variables. J. Lumbini. Med. Coll. Vol 4, No 2, July-Dec 2016, page: 94-98 DOI: https://doi.org/10.22502/jlmc.v4i2.99